Chronic kidney disease prevalence and ambulatory blood pressure profile in healthy HIV positive subjects pre and post anti-retroviral therapy - Borkum, Megan Sara (Division of Nephrology and Hypertension, 2016)
Introduction: Few studies have been done in South Africa to establish the extent of chronic kidney disease (CKD) in stable outpatients infected with the human immunodeficiency virus (HIV). Both HIV and the anteretroviral therapy (ART) used to treat HIV have been associated with abnormal metabolic profile, increased cardiovascular risk and renal disease1,2,3. Hypertension has been found to be common in HIV infected individuals, in European and American cohorts, with a prevalence ranging from 13- 34%2. Nocturnal blood pressure (BP) is superior to daytime or office BP as a predictor of cardiovascular disease4. However, the relationship between circadian BP patterns, measured via ambulatory blood pressure (ABP) monitoring, and HIV has never been documented in the South African HIV infected population. Individuals with an abnormal diurnal rhythm and a blunted nocturnal decline in systolic BP (SBP), i.e. ≤ 10%, are referred to as 'non- dippers' and have the highest risk of cardiovascular complications4. HIV itself has been associated with a non- dipping status and may play a role in the HIV related increase in cardiovascular risk5.